Warming under seminatural outdoor conditions in the larval stage negatively affects insect flight performance. (31st May 2018) - Tüzün, Nedim; Op de Beeck, Lin; Oliarinony, Ranalison; Van Dievel, Marie; Stoks, Robby
Abstract : Laboratory studies indicate global warming may cause changes in locomotor performance directly relevant for fitness and dispersal. Yet, this remains to be tested under seminatural settings, and the connection with warming-induced alterations in the underlying traits has been rarely studied. In an outdoor mesocosm experiment with the damselfly Ischnura elegans, 4°C warming in the larval stage decreased the flight muscle mass, which correlated with a lower flight endurance. Warming did not affect body mass, size or wing morphology. This illustrates how carry-over effects of warming under seminatural conditions during early development bridge metamorphosis and negatively impact locomotor performance through changes in a key flight-related trait.